Κτῆμα ἐς ἀεί. Überlegungen zu Eigentum und Historiographie in den Plinius-Briefen - Felgentreu, Fritz (Hyperboreus, 2015)
In his epistles, Pliny opposes an individual concept of perpetual ownership to the standard philosophical refutation of its possibility or even desirability. In order to convey his ideas, Pliny describes his Tuscan villa in terms that not only portray this piece of real estate as an ideal example of aristocratic property, but also turn the object as it existed in reality into a literary one, thereby perpetuating his spiritual ownership indeﬁnitely. As can be shown from the eulogy of Corellius Rufus, the idea that the literary product of an author’s creativity will remain his property forever is closely connected to the way Pliny characterizes his epistolary project as an antithesis to the other great genre of contemporary Latin prose, historiography. Thus, Plinian epistolography is as preoccupied with creating a κτῆμα ἐς ἀεί as historiography has been since Thucydides coined the phrase.